Pengaruh Penerapan Sistem Informasi Rumah Sakit Generik Open Source (Simrs Gos) Dan Lingkungan Kerja Terhadap Kinerja Perawat Melalui Kepuasan Kerja Pada Rumah Sakit Umum M. Natsir Solok - Ivan Maulana; Zefri Yenni; Yamasitha . (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to determine the effect of the implementation of the Generic Open Source Management Information System (SIMS GOS) and the work environment on nurse performance through job satisfaction at M. Natsir General Hospital, Solok City. Data collection was conducted through a survey and the distribution of a Google Form link, with a sample of 77 respondents. The analysis methods used were the measurement model (Outer Model) and the structural model (Inner Model). The results obtained based on the measurement model (Outer Model) and the structural model (Inner Model) showed: There is a significant effect of information system implementation on job satisfaction. There is a significant effect of the work environment on job satisfaction. There is an insignificant effect of the work environment on nurse performance. There is a significant effect of the work environment on employee performance. There is a significant effect of job satisfaction on nurse performance. There is a significant effect of information system implementation on nurse performance through job satisfaction. There is a significant effect of the work environment on nurse performance through job satisfaction.